Effect of various crop establishment methods and herbicides on growth and yield of rice - Mukherjee, Dhiman (Journal of Cereal Research, 2019)
Emphasis on the climate resilience cropping system under Indian agriculture system is vital to the livelihood security of many small and marginal farmers in the country, mainly who depend as rice their staple food. Devising suitable adaptation strategies will facilitate farmers to handle with various climate risks and promote efficient use of limited available resources to bring sustainability to farm production and stability to their incomes. Rice (Oryza sativa L.), covered about 42 m ha and accounts for about 103.61 million tonnes of the country’s total food grain production and globally is a popular crop (Tomar et al., 2018). Under Indo-Gangetic Plains (IGP), transplant of rice crop requires high amount of water for puddling process to avert seepage losses. However, the wet tillage destroys the soil structure and also huge labour force is required for transplanting. Direct seeded rice (DSR) is an alternative to transplanted rice. This technique evade the main crisis faced in West Bengal i.e., manpower scarcity for transplanting due to peak demand. Moreover, under shortage of irrigation water and delayed monsoon, DSR is better option. This helps timely sowing of the following mustard, wheat or other rabi crops (Mukherjee, 2016). Jat et al. (2014) found that 7-10% reduction in wheat yield when sown after transplanted rice compared with when sown after DSR in non-puddled conditions. However, with the change in paddy cultivation practices, weed invasion and crop-weed competition are predicted to increase and will remain to be a primary challenge s for enhancing and maintaining high yield potential (Mukherjee and Mandal, 2017). Yield loss of rice observed to the extent of 40 to 65% due to weed competition (Yakadri et al., 2016). Keeping this aspect in mind present investigation was conducted, with the objective to optimize rice yield under different crop establishment method with various chemical control options. DOI: https://doi.org/10.25174/2249-4065/2019/95811